2011
DOI: 10.1242/jcs.078519
|View full text |Cite
|
Sign up to set email alerts
|

Reassessment of the role of plasma membrane domains in the regulation of vesicular traffic in yeast

Abstract: SummaryThe Saccharomyces cerevisiae plasma membrane has been proposed to contain two stably distributed domains. One of these domains, known as MCC (membrane compartment of Can1) or eisosomes, consists of furrow-like membrane invaginations and associated proteins. The other domain, called MCP (membrane compartment of Pma1), consists of the rest of the membrane area surrounding the MCC patches. The role of this plasma membrane domain organization in endocytosis is under debate. Here we show by live-cell imaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
99
2
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(114 citation statements)
references
References 29 publications
10
99
2
3
Order By: Relevance
“…Using the GFP-PH Plcd -PH Plcd -GFP reporter we observed enrichment of PtdIns(4,5)P 2 throughout the plasma membrane of small buds with 2-3-fold the concentration of PtdIns(4,5)P 2 in the bud compared to the back of the mother cells. Previous studies have shown using the inositolpolyphosphate 5-phosphatase synaptojanin Sjl2p and the ANTH domain from Sla2p to visualize PtdIns(4,5)P 2 that this phospholipid is localized to endocytosis sites which are concentrated in small buds (Sun et al, 2007;Brach et al, 2011). The loss of PtdIns(4,5)P 2 polarity in the mss4-f12 cells is consistent with the suggestion that membrane traffic via endocytosis and exocytosis is important for invasive growth.…”
Section: Discussionsupporting
confidence: 84%
“…Using the GFP-PH Plcd -PH Plcd -GFP reporter we observed enrichment of PtdIns(4,5)P 2 throughout the plasma membrane of small buds with 2-3-fold the concentration of PtdIns(4,5)P 2 in the bud compared to the back of the mother cells. Previous studies have shown using the inositolpolyphosphate 5-phosphatase synaptojanin Sjl2p and the ANTH domain from Sla2p to visualize PtdIns(4,5)P 2 that this phospholipid is localized to endocytosis sites which are concentrated in small buds (Sun et al, 2007;Brach et al, 2011). The loss of PtdIns(4,5)P 2 polarity in the mss4-f12 cells is consistent with the suggestion that membrane traffic via endocytosis and exocytosis is important for invasive growth.…”
Section: Discussionsupporting
confidence: 84%
“…The lipid composition of the plasma membrane is apparently also monitored by the MCC transmembrane protein Nce102, which signals the two Pkh kinases (Fr ö hlich et al, 2009 ). As expected, the deletion of PIL1 leads to a loss of the MCC compartments, with a homogenous distribution of the respective membrane proteins within the plasma membrane and the accumulation in one or a few clusters of the ' eisosome remnants ' , which are only detectable in the later stages of cell growth (Brach et al , 2011 ). Surprisingly, the loss of the closely related Lsp1 function does not cause a disassembly of the eisosomes and the MCC microcompartment, indicating subtle functional differences.…”
Section: Eisosomessupporting
confidence: 61%
“…Consistent with this observation, the position of the eisosomes in Ashbya gossypii , a filamentous fungus closely related to S. cerevisiae , did not coincide with the bulk of the endocytic traffic at the hyphal tip, but they rather accumulated in the subapical tip regions (Seger et al , 2011 ). In vivo photobleaching experiments in S. cerevisiae suggest that the organization of the MCC compartments within the yeast plasma membrane has no influence on the intracellular vesicle trafficking, also opposing a function in endocytosis (Brach et al , 2011 ). In fact, both endocytosis and exocytosis were found to be restricted to the MCP microcompartment, independent of the position of the neighboring MCC patches.…”
Section: Eisosomesmentioning
confidence: 76%
“…At a smaller spatial scale the endocytic events in yeast appear random, except that they are excluded from plasma membrane regions that are in contact with cortical endoplasmic reticulum (Stradalova et al 2012) and from eisosomes, stable microdomains of the fungal plasma membrane (Brach et al 2011). The exclusion of endocytosis from these regions is most likely attributable to steric hindrance inhibiting bud nucleation.…”
Section: The Cell-wide Spatial and Temporal Dynamics Of Ccp Nucleationmentioning
confidence: 99%